Common Fetal Outcome among Women with Short Interpregnancy Interval: Fetal Outcome with Short Interpregnancy Interval - Rehman, Anmol Ur; Jehangir, Sidra; Rehman, Fizza (Pakistan Journal of Health Sciences, 2025)
The interpregnancy interval (IPI) is the time between the previous childbirth and the subsequent gestation. The short IPI is known for having adverse effects on fetal outcomes. Objectives: To investigate the association of short IPI ≤18 months. Methods: This cross-sectional study was conducted in the Obstetrics and Gynecology Department of Northwest General Hospital, Peshawar, and it lasted for more than six months. Participants were 126 women (15 to 45 years) with singleton pregnancies and IPI ≤ 18 months. Adverse outcomes, which include preterm birth, low birth weight, stillbirth, and early neonatal death, were analyzed using multivariable logistic regression. Results: 68(54%) women experienced at least one adverse fetal outcome, including low birth weight 27(21%), premature births 25(20%), stillbirths 11(9%), and early neonatal death 5(4%). Additionally, younger mothers (15 to 19 years) had the highest rates of preterm birth 7 35%) and low birth weight 6 28%). Multi variable logistic regression (confounding factors age, parity, education and residence) showed short IPI (<6 months) was strongly associated with early birth (aOR 8.62, 95% CI 1.53-48.51, p=0.014) and short IPI (6-11 months) also increased early birth risk (aOR 6.28, 95% CI 1.10-35.89, p=0.039). For underweight neonates, short IPI (6-11 months) had an elevated risk (aOR 7.22, 95% CI 1.90-27.47, p=0.004). Associations with stillbirth and neonatal death were not significant after adjustment. Conclusions: To reduce these risks, comprehensive family planning programs, maternal health education, and antenatal counselling on optimal birth spacing need to be prioritized in developing countries like Pakistan.